2011
DOI: 10.1007/s13142-011-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social determinants on evidence-based behavioral interventions—considerations for implementation in community settings

Abstract: Over the last decade, the Centers for Disease Control and Prevention's Diffusion of Effective Behavioral Interventions (DEBI) program funded several hundred community-based organizations (CBOs) and health departments in a wide-scale HIV prevention national diffusion effort. We interviewed six California agencies funded to implement one of three group-level DEBIs to identify facilitators and/or challenges to effective implementation. We identified several social and structural factors affecting community member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Program fit is consistently identified as important to successful program implementation [47] and represents a potential point of intervention in efforts to increase program fidelity. Although a number of HIV prevention studies have shown that poor program-client fit by agencyimplemented programs results in low program fidelity [42,[48][49][50][51][52][53], none of this work has examined selfimplemented programs.…”
Section: Overviewmentioning
confidence: 99%
“…Program fit is consistently identified as important to successful program implementation [47] and represents a potential point of intervention in efforts to increase program fidelity. Although a number of HIV prevention studies have shown that poor program-client fit by agencyimplemented programs results in low program fidelity [42,[48][49][50][51][52][53], none of this work has examined selfimplemented programs.…”
Section: Overviewmentioning
confidence: 99%
“…In their editorial addressing social determinants of health in the prevention and control of HIV/AIDS and other communicable diseases, Dean and Fenton (2010) argue that it is ''increasingly unacceptable for those planning and delivering prevention services to claim that addressing SDH is outside of their jurisdiction, thereby absolving themselves of further action'' (p. 4). Gandelman and Dolcini (2012) propose both short-term and long-term strategies to address social determinants of sexual health including incorporating job skills training into existing evidence-based interventions, providing housing assistance for homeless or displaced persons, implementing microfinance programs (Sherman et al 2006), and longer-term strategies that reduce poverty, and sustain improved educational opportunities, stable housing, and healthcare access. In addressing the adverse effects of homelessness on the health of people living with HIV/AIDS, the CDC, in collaboration with the Department of Housing and Urban Development (HUD), found that providing rental assistance to homeless and unstably housed persons living with HIV/AIDS was associated with positive outcomes for housing status, health care utilization, and mental and physical health in a randomized controlled trial (Wolitski et al 2010).…”
Section: Study Implicationsmentioning
confidence: 99%
“…The term ''social determinants'' and ''structural determinants'' of health are often used interchangeably and have come to be known as any approach that attempts to alter the environment in which health risk occurs. These approaches involve policies that address the conditions in which individuals live (e.g., poverty, unemployment, inadequate educational and health resources), and can include policy, legal, and microfinance interventions (Dean and Fenton 2010;Gandelman and Dolcini 2012). The World Health Organization's (WHO) Commission on Social Determinants of Health (2008) proposed that interventions targeting social and structural barriers to health aim to improve daily living conditions and address the inequities in the distribution of money, resources, and power.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Prior work examining HIV program fidelity has identified a number of fidelity challenges at the program level (e.g., training, client fit, procedural fit) [13,14,17,[24][25][26][27][28][29]. However, past studies have not examined how agencies adapt to economic strains and the influence of those adaptations on program fidelity.…”
Section: Program Fidelitymentioning
confidence: 99%